Corrosion of Fe-2%Mn-0.5%Si Steels at 600-800℃ in N_2/H_2O/H_2S Atmospheres - 김민정; 박상환; 이동복 (한국표면공학회, 2011)
Fe-2%Mn-0.5%Si alloys were corroded at 600, 700 and 800℃ for up to 70 h in 1 atm of N2 gas, or 1 atm of N_2/H_2O-mixed gases, or 1 atm of N_2/H_2O/H_2S-mixed gases. Oxidation prevailed in N2 and N_2/H_2O gases,whereas sulfidation dominated in N_2/H_2O/H_2S gases. The oxidation/sulfidation rates increased in the order of N_2 gas, N_2/H_2O gases, and, much more seriously, N_2/H_2O/H_2S gases. The base element of Fe oxidized to Fe_2O_3and Fe_3O_4 in N_2 and N_2/H_2O gases, whereas it sulfidized to FeS in N_2/H_2O/H_2S gases. The oxides or sulfides of Mn or Si were not detected from the XRD analyses, owing to their small amount or dissolution in FeS. Since FeS was present throughout the whole scale, the alloys were nonprotective in N2/H2O/H2S gases.